Molecular investigation of candidate genes for pyroptosis-induced inflammation in diabetic retinopathy - Wang, Nan; Ding, Lexi; Liu, Die; Zhang, Quyan; Zheng, Guoli; Xia, Xiaobo; Xiong, Siqi (Frontiers in Endocrinology, 2022)
Background: Diabetic retinopathy is diabetic microvascular complication. Pyroptosis, as a way of inflammatory death, plays an important role in the occurrence and development of diabetic retinopathy, but its underlying mechanism has not been fully elucidated. Methods: We obtained mRNA expression profile datasets GSE60436 from Gene Expression Omnibus (GEO) database and collected 51 pyroptosis-related genes from Pubmed database. The differentially expressed pyroptosis-related genes were obtained by bioinformatics analysis with R software, and then 8 key genes of interest were identified by correlation analysis, gene ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and protein-protein interaction (PPI) network analysis. Then, the expression levels of these key pyroptosis-related genes were validated with the quantitative real-time polymerase chain reaction (qRT-PCR) in human retinal endothelial cells with high glucose incubation, which was used as in vitro model of diabetic retinopathy. Finally, the ceRNA regulatory network was structured. Results: A total of 13 differentially expressed pyroptosis-related genes were screened, including 1 down-regulated gene and 12 up-regulated genes. Correlation analysis showed that there was a correlation among these genes. Then KEGG pathway and GO enrichment analyses were performed to explore the functional roles of these genes. In addition, 8 hub genes were identified by PPI network analysis using Cytoscape software. Verified by qRT-PCR, the expression of all these 8 hub genes in the in vitro model of diabetic retinopathy were consistent with the results of bioinformatics analysis of mRNA chip. Finally, 20 miRNAs were predicted to target 3 key genes and 22 lncRNAs were predicted to potentially bind to these 20 miRNAs. Then, we constructed a key ceRNA network that is expected to mediate cellular pyroptosis in diabetic retinopathy. Conclusion: Through the data analysis of GEO database by R software and verification by qRT-PCR and validation set, we successfully identified potential pyroptosis-related genes involved in the occurrence of diabetic retinopathy. The key ceRNA regulatory network associated with these genes was structured. These findings might improve the understanding of molecular mechanisms underlying pyroptosis in diabetic retinopathy.